Răspuns :
[tex] \frac{x}{y} = \frac{12}{7} =\ \textgreater \ x=12k~si~y=7k.[/tex]
[tex] \frac{ x^{2}- y^{2} }{ x^{2} + y^{2} } = \frac{(12k) ^{2} - (7k)^{2} }{(12k) ^{2}+ (7k)^{2} } = \frac{144 k^{2}-49 k^{2} }{ 144k^{2}+49k ^{2} } = \frac{95k ^{2} }{193 k^{2} } = \frac{95}{193} .[/tex]
[tex] \frac{ x^{2}- y^{2} }{ x^{2} + y^{2} } = \frac{(12k) ^{2} - (7k)^{2} }{(12k) ^{2}+ (7k)^{2} } = \frac{144 k^{2}-49 k^{2} }{ 144k^{2}+49k ^{2} } = \frac{95k ^{2} }{193 k^{2} } = \frac{95}{193} .[/tex]
x=12y/7 ⇒x2 = 144y patrat/49
144y2/49 - 49y2/49 = 95y2/49
144y2/49 + 49y2/49 = 193y2/49
⇒95y2/49 x 49/193y2 ⇒95/193